Additive Main effect and Multiplicative Interaction (AMMI) model analysis for yield performance and G×E interaction in a multi-environmental trial of aromatic fine rice in Bangladesh - Islam, Shams Shaila; Hasan, Ahmed Khairul; Khaldun, Abul Bashar Mohammad; Nazir, Novizar (Journal of Cereal Research, 2021)
The problem of genotype-environment interaction (G×E) in interpreting multilocus trial analyses and predicting genotype performance can be mitigated by applying Additive Main effect and Multiplicative Interaction (AMMI) model analysis. The model AMMI was used in the present study to determine the effect of genotype, environment, and their interaction, to determine the extent of G×E interaction and to identify the factors contributing to G×E interaction for the best yielding aromatic fine rice genotype grown in four different districts in Bangladesh. Analysis of variance showed that the effect of genotypes, environments, G×E interactions were highly significant for plant height, days to maturity, panicles length, grain yield. Result showed grain yield had highly significant differences for environmental traits like (soil properties, phenological, genotypes) with their interactions which indicated that environments were different and changeability with the genotypes. Large variations in total P, Fe and rainfall identified as the main cause of the observed interaction. Here, Genotype BRRI Dhan34 had the highest mean grain yield values over four locations, respectively. In AMMI model, among four locations Dinajpur with Nilphamari were the majority responsive environments and Dinajpur was the most adjacent responsive location. Therefore, location Dinajpur with BRRI Dhan34 genotype could be considered as a better combination for higher grain yield among the ten aromatic fine rice genotypes.